What Do We Know about the Influence of Agricultural Support on Agricultural Land Prices? - Paul Feichtinger; Klaus Salhofer (German Journal of Agricultural Economics (GJAE), 2013)
This study gives an overview of the theoretical foundations, the empirical procedures and the derived results of the literature on the determinants of agricultural land prices. A particular interest is given to the effects of government support policies. Almost all empirical studies on the determination of land prices either refer to the net present value method or the hedonic pricing approach. While the two approaches have different theoretical basis, they converge in their empirical implementation. Empirical studies use a broad range of variables to explain land values and we systematise these into six categories. In order to investigate the influence of different measures of government support on land prices, a meta-regression analysis is carried out based on 242 observations from 26 articles. Results indicate that a 10% decrease of agricultural support would decrease land prices by 3.3% to 5%. Therefore, a considerable part of farm subsidies is realized by initial owners of land instead of operating farmers. Results in regard to differences in capitalization for different support measures are ambiguous. Model assumptions, data structure and estimation techniques do have a significant influence on capitalization estimates.
Keywords: 330; Agrarsubvention; Immobilienpreis; Landwirtschaftliche Immobilien; Hedonischer Preisindex; Meta-Analyse